(untitled) (International Journal of Technology and Management Research, 2020)
The study set out to examine the influence of motivation on teacher job performance and on teacher retention in the Somanya Circuit of the Ghana Education Service. Generally, teachers in Ghana tend to leave the teaching profession despite various interventions such as single salary spine and best teacher award scheme put in place. Teachers in the Somanya Circuit did not stay and work for more than three years but there is no documented reason why. Therefore the study was done to find out why and whether they were not motivated enough. The researcher adopted the descriptive survey design. A sample of 170 teachers selected by stratified random sampling was used. Questionnaires was the main instrument used and the data collected were analysed with the statistical tool SPSS. The findings of the study revealed that basic school teachers in public school in the Somanya circuit were highly motivated, but they rated their mode of promotion and salary levels to be rather low. The results also revealed that respondents generally disagreed that the factors of motivation like salary and monetary compensation, leave benefits, good retirement plan, promotion, job security, opportunities for extra income, health benefits, accommodation, free time during holidays and more time to attend to other issues do influence their level of motivation. It was further revealed that some basic school teachers have been retained in the Somanya circuit not necessarily based on the motivation avenues presented to them but on other factors Finally, it was recommended that Yilo Krobo Municipal Directorate of the Ghana Education Service should continue to motivate teachers by providing adequate supervision, recognition and appreciation to motivate basic school teachers in the Circuit. Citation: E, Owusu-Acheaw, and D., Bakker-Edoh. Influence of Job Motivation on Basic School Teacher Retention in the Somanya Circuit of Eastern Region in Ghana Education Service, 2020; 5(3): 12-36. Received: April 8, 2020 Accepted: September 30, 2020